TRACES OF CULTURES IN ENGLISH TEXTBOOKS FOR PRIMARY EDUCATION - Hermawan, Budi; Lia, Noerkhasanah (Indonesian Journal of Applied Linguistics, 2012)
Abstract: The inseparability of language and culture has become a rich source of investigation in the field of English Language Teaching. Possible topics may be focused among others, on how culture is packaged and presented, whose culture is disseminated, is there, if any, local culture preserved and disseminated in textbooks which often serve as the main English language learning material. Learning material can often carry cultural content (see McGrath: 2002) which can refer to Source Cultures, Target Culture, or International Target Culture (Cortazzi and Jin 1999). Culture is often about wisdoms and worldview of the country and textbooks can be a good source for students to learn and adopt these wisdoms and worldview, and develop their cultural awareness and identity. Relying on this, the present study investigates whose culture the textbooks investigated disseminate, how culture is disseminated in the textbooks, and whether local culture is also preserved and disseminated. The study is descriptive qualitative in nature. It employs a systematic technique for analyzing message content and message handling. Element of quantitative in the form of how the data are recorded in percentages has also been used. The data for this study are collected from three English textbooks for primary schools entitled â€œGrow with Englishâ€, book four to six published by Erlangga. The data for the study are in the form of written texts and illustrations that may accompany the reading passages. The reading passages are categorized and analyzed based on the framework of Culture in Four Senses proposed by Adaskou, Britten, and Fahsi (1990). The study finds that Target Culture is more salient and disseminated in the textbooks, while Local Culture when present is presented in the form of, among others, names chosen for the characters, places and locations discussed in reading passage, and rituals. Â  Kata kunci: Culture, Cultural awareness and identity, Four sense of culture, Textbooks. Â